2010
DOI: 10.1007/s11060-010-0466-4
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistent blood brain barrier disruption by intraarterial mannitol in rabbits: implications for chemotherapy

Abstract: The novel ability to quantify drug and tracer concentrations in vivo by optical means leads to the possibility of detecting and quantifying blood brain barrier (BBB) disruption in real-time by monitoring concentrations of chromophores such as Evan's Blue. In this study, experiments were conducted to assess the disruption of the BBB, by intraarterial injection of mannitol, in New Zealand white rabbits. Surgical preparation included: tracheotomy for mechanical ventilation, femoral and selective internal carotid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 50 publications
2
53
0
Order By: Relevance
“…7 In parallel studies, we had observed that BBBD in rabbits with IA mannitol was highly variable. 11,12 Similar variability in the degree of BBBD has also been reported in human subjects. 13 Such variability could have a very significant impact on the delivery of chemotherapeutic drugs that require BBBD.…”
Section: Introductionsupporting
confidence: 72%
“…7 In parallel studies, we had observed that BBBD in rabbits with IA mannitol was highly variable. 11,12 Similar variability in the degree of BBBD has also been reported in human subjects. 13 Such variability could have a very significant impact on the delivery of chemotherapeutic drugs that require BBBD.…”
Section: Introductionsupporting
confidence: 72%
“…As the BBBD process can be highly variable between animals (for discussion on this topic, see Joshi et al 13 ), a large number of animals had to be included in each subgroup for this experiment. The data shown in Figure 2 represent the peak Gadomer concentration (mmol/L) in the treated hemisphere of animals injected at a specific delay after the BBBD procedure (Table 1).…”
Section: Characterization Of the Dynamic Blood-brain Barrier Disruptimentioning
confidence: 99%
“…10 One major weakness of this therapeutic strategy remains the intersubject variability in the BBB permeability; this is accompanied by an inherent difficulty in predicting and evaluating the extent of this permeability. 13 The extent of BBBD in preclinical studies has traditionally been studied with ex vivo brain samples using an Evan's blue staining technique, and consequently do not allow the follow-up of the animals. [13][14][15][16][17] Few studies have looked at the dynamic process of the BBBD, and the methodology used in these experiments typically required harvesting brain specimens at each time point, thereby preventing a longitudinal observation in a single subject.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,23,28,29 SFDI measurements could be introduced through a cranial window for the in vivo spatial mapping of brain pharmacokinetics. Data from spatially resolved pharmacokinetics could be used to develop multicompartment models for plasma and tissue concentrations in larger animal models where space is more appropriate for the limited resolution of the concentration maps.…”
Section: Evaluation Of Mitoxantrone Delivery To Brain Tumormentioning
confidence: 99%